Cyanoacrylate application on colonic anastomosis: is it safe or not? - Güngör, Gürhan; Demiral, Gökhan; Şenol, Metin; Bayraktar, Barış; Çelik, Yahya; Bölük, Salih (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction : Major complications of colonic anastomosis include fistula, bleeding, and anastomotic stricture, and the most common one is anastomotic leakage. Many organic or inorganic tissue adhesives are being used such as fibrin glue or cyanoacrylate to strengthen or protect colonic anastomosis. Up to now, a great number of studies have been carried out to investigate the effects of these biomaterials. Aim : To determine the effect of cyanoacrylate application on anastomosis safety. Material and methods : In this experimental study, rats were divided into two groups; a control group and an experimental group. Full-thickness incisions were done on the left colon of the rats, and then end-to-end anastomosis was performed by using 5/0 silk separated sutures. In the experimental group we applied cyanoacrylate over the sutures. The samples were taken on the 7th day. Results : In the control group the average tissue hydroxyproline levels and the average bursting pressures were significantly higher than in the experimental group. Conclusions : The purpose of all the experimental studies is to prevent and reduce anastomotic complications. Despite all the studies that have been done, colonic anastomosis complications continue to be a problem. As a result, we suggest that cyanoacrylate has a negative effect on the healing process of colonic anastomosis.